Machines of Tomorrow: Exploring AI-Human Relationships in Contemporary Literature (Knowledgeable Research A Multidisciplinary Journal, 2026)
The rapid development of artificial intelligence has transformed how we perceive technology’s role in shaping human life. Beyond its technical applications, AI has emerged as a profound subject in literature, raising critical questions about identity, morality, and the future of humanity. Fictional narratives often serve as a lens through which societies reflect on the ethical dilemmas and emotional complexities surrounding AI integration into everyday life. This paper examines the complex dynamics between artificial intelligence (AI) and humanity as depicted in contemporary literature. By focusing on Ian McEwan’s Machines Like Me, the study interrogates how AI challenges traditional notions of identity, ethics, and agency. It explores questions such as: Can AI possess consciousness? How does AI disrupt human relationships? What does AI mean for humanity’s future? The novel offers a rich examination of ethical dilemmas, human emotions, and the boundaries between human and machine, set against an alternate history of technological advancement. By analyzing AI’s capacity for consciousness, morality, and emotional engagement, the paper interrogates the societal and philosophical implications of AI’s integration into human lives and tries to explore how literature critiques and reimagines humanity’s future in an AI-dominated world. The analysis combines posthumanism and ethical philosophy to critically assess these representations, offering insights into the socio-political implications of a world increasingly defined by AI.
Keywords: Artificial Intelligence, Ethics, Posthumanism. *Corresponding